Genomic Analysis and Antimicrobial Resistance of Aliarcobacter cryaerophilus Strains From German Water Poultry - Müller, Eva; Hotzel, Helmut; Ahlers, Christine; Hänel, Ingrid; Tomaso, Herbert; Abdel-Glil, Mostafa Y. (Frontiers in Microbiology, 2020)
Aliarcobacter cryaerophilus (formerly Arcobacter cryaerophilus) is a globally emerging foodborne and zoonotic pathogen. However, little is known about the species' genomic features and diversity, antibiotic resistance and virulence. In this study, 27 A. cryaerophilus strains from water poultry in Thuringia, Germany, were investigated using whole-genome sequencing. Four of these strains were sequenced using long- and short-read sequencing methods to obtain circularized genomes. The German strains belong to the A. cryaerophilus cluster I. Cluster I genomes exhibited a high degree of genetic diversity in which variable sites comprised 9.1% of the core genome. The German strains formed three subgroups that contained 2, 6, and 9 strains, respectively. The genomic analysis of cluster I revealed variable presence of mobile elements and that 65% of the strains lack CRISPR systems. The four circularized genomes carried a ~2 Mbp chromosome and a single megaplasmid (size 98.1-154.5 Kbp). The chromosome was densely packed with coding sequences (~92%) and showed inversions and shifts in the gene blocks between different strains. Antimicrobial resistance was assessed using a gradient strip diffusion method and showed that all 27 strains were resistant to cefotaxime and susceptible to erythromycin, gentamicin, and ampicillin. Sixteen strains were also resistant to ciprofloxacin, whereas 23 were resistant to streptomycin. The genetic prediction of antibiotic resistance identified numerous efflux pumps similar to those found in A. butzleri. All strains harbored two beta-lactamase genes which may explain the cefotaxime resistance. A correlation between the gyrA point mutation (Thr-85-Ile) and ciprofloxacin resistance was partially discovered in 15 out of 16 strains. In silico virulence profiling showed a wide range of virulence factors including a full chemotaxis system and most of the flagellar genes. In contrast to A. butzleri, no urease cluster was found. This study provides new insights into the genomic variability of A. cryaerophilus strains of cluster I. The different genetic makeup of these strains may contribute to the virulence of strains and the severity of the infections in humans.